2022
DOI: 10.1017/s1930297500008950
|View full text |Cite
|
Sign up to set email alerts
|

The advice less taken: The consequences of receiving unexpected advice

Abstract: Although new information technologies and social networks make a wide variety of opinions and advice easily accessible, one can never be sure to get support on a focal judgment task. Nevertheless, participants in traditional advice taking studies are by default informed in advance about the opportunity to revise their judgment in the light of advice. The expectation of advice, however, may affect the weight assigned to it. The present research therefore investigates whether the advice taking process depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Second, advice and initial judgments are non-orthogonal. For instance, multiple regression with partial effects would be more appropriate than traditional analysis approaches for experimentally manipulated advice distance (e.g., Rebholz & Hütter, 2022;Schultze et al, 2015). Moreover, non-orthogonality is highly ecological as judges often anchor advisors by including their own judgments in their requests for advice (Reif et al, 2022).…”
Section: Unconstrained Regressionmentioning
confidence: 99%
“…Second, advice and initial judgments are non-orthogonal. For instance, multiple regression with partial effects would be more appropriate than traditional analysis approaches for experimentally manipulated advice distance (e.g., Rebholz & Hütter, 2022;Schultze et al, 2015). Moreover, non-orthogonality is highly ecological as judges often anchor advisors by including their own judgments in their requests for advice (Reif et al, 2022).…”
Section: Unconstrained Regressionmentioning
confidence: 99%
“…Compared to the inter‐individual differences in advice weighting trueτ^Ak,S$$ {\hat{\tau}}_{A_k,S} $$, there was notably less variability for different items as measured by trueτ^Ak,T$$ {\hat{\tau}}_{A_k,T} $$. Also in comparison to other judgment tasks, such as product carbon footprint or quantity estimation (Rebholz & Hütter, 2022; see also Rebholz, 2023, Chapter 3, for MER‐WOAs), the differences between items were rather negligible. In contrast to the item‐wise random effects, we indeed found significant differences between some of the participant‐wise random effects.…”
Section: Resultsmentioning
confidence: 96%
“…Second, advice and initial judgments are non‐orthogonal. For instance, multiple regression with partial effects would be more appropriate than traditional analysis approaches for experimentally manipulated advice distance (e.g., Schultze et al, 2015; Rebholz & Hütter, 2022). Moreover, non‐orthogonality is highly ecological as judges often anchor advisors by including their own judgments in their requests for advice (Reif et al, 2022).…”
Section: Beyond Relativity To the Selfmentioning
confidence: 99%
“…Expectations have also been shown to influence advisees. In particular, Rebholz and Hütter (2022) found that advisees weigh less a piece of advice when it is not expected.…”
Section: Discussionmentioning
confidence: 99%